School Adjustment, Locus of Control and Achievement Motivation as Predictor of Test Anxiety - Stella, Ogbogo; Amaechi-Udogu, Vivian (International Journal of Scientific Research and Management (IJSRM), 2019)
The study investigated school adjustment, locus of control and achievement motivation as predictor of test anxiety amongst secondary school students in obio-Akpor LGA in Rivers State Nigeria. Five research questions and four null hypotheses were formulated to guide the study Multiple prediction design within the correlational research design was employed for the study, the population of the study was 10,705 junior secondary school students (JSS1) in 14 schools in Obio-Akpor Local Government Area 0f Rivers state. Stratified sampling technique based on gender was used to obtain the sample size of 388 (male 190 and female 198). Four valid instruments titled; Test Anxiety Questionnaire (TAQ), Locus of Control Questionnaire (LOCQ), School Adjustment Questionnaire (SAQ) and Achievement Motivation Questionnaire (AMQ) were used for the study.  The reliability and construct validity of these instruments were estimated using the internal consistency method of Cronbach alpha. For Test Anxiety Questionnaire, Cronbach Alpha reliability coefficient was .846, for Locus of Control Questionnaire it was .618, for Achievement Motivation Questionnaire, it was .545 and for School Adjustment it was .611. Research question 1, was answered using descriptive statistics of mean and standard deviation, while 2, 3, 4 and 5 were answered using simple and multiple regression.  At 0.05 level of significance, ANOVA associated with multiple regression and t-test associated with simple regression was used for testing the null hypothesis. The result revealed that test anxiety of secondary school students was high, school adjustment and achievement motivation predict test anxiety significantly with locus of control predicting test anxiety but not significantly. Jointly, school adjustment, locus of control and achievement motivation predicted test anxiety significantly. Based on findings recommendations were made.